A pedicled buccal periosteal flap for the closure of oro-antral fistula - Marwa T. Ibrahim; Eslam A. Gharieb; Mona S. Sheta (BMC Oral Health, 2024)
Abstract Background An oroantral fistula is a communication between the maxillary antrum and oral cavity. This pathological communication is formed mainly due to dental extraction of maxillary premolars and molars. Adequate management should include closing the oroantral fistula and eliminating sinus infections to prevent recurrence and sinusitis. Purpose This study aimed to evaluate the effectiveness of using the pedicled buccal periosteal flap for closing an oroantral fistula without changing the native intraoral structure. Patients & Methods Patients with oroantral fistulas were included in this study. The patients were examined clinically by Valsalva test and cheek-blowing test, the hole was probed, and the extent of the underlying bone defect was determined radiographically using computed tomography preoperatively. All patients underwent surgical closure of oroantral fistula using a pedicled buccal periosteal flap. Results All 10 patients obtained satisfactory results with marked improvement in the function of the maxillary sinus and complete healing of oroantral fistula with no recurrence except in Case No. 5, who had a recurrence of the oroantral fistula, also there was no statistically significant difference between the vestibular depth preoperatively and postoperatively. Conclusion A pedicled buccal periosteal flap is a novel technique for oroantral fistula closure as it preserves vestibular depth with a tension-free closure flap and harbors the advantages of the regenerative potential of the periosteum. Registration date 14/8/2023 Registration number NCT05987943